(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The Syrian economy has suffered from the phenomenon of rising prices to varying degrees since the 1970s, but the rates of the general level of prices have accelerated significantly in recent years as a result of internal and external factors related to the crisis in the country, which significantly on the exchange rate of the Syrian pound against the US dollar, which caused It negatively affected the economic and social life of individuals and activities, especially low-income people. Therefore, knowing the movement and trends of prices of goods and services in the future helps decision-makers to develop appropriate policies to achieve the stability of the general level of prices and improve living standards. The research aims to forecast consumer price index for the coming period based on consumer price index data and link it to the US dollar exchange rate for the period (2011-2019). The results of the analysis showed that the rise in the exchange rate will lead to greater imported inflation, and predictions play an important role in explaining the continuous rise in prices level, and a model capable of forecasting significantly up to a period of three months can be used.